EKSISTENSI SENI KETUK TILU KELOMPOK LINGKUNG SENI DAYA SUNDA DI KEBUN BINATANG BANDUNG - Reffali, Soni; Jaenudin, Nanang (LP2M ISBI Bandung, 2023)
Since the year 1970, Ketuk Tilu of Lingkung Seni Daya Sunda has been able to maintain and expand his presence in Bandung Zoo. The goal of this research is to identify the factors that contribute to Ketuk Tilu Lingkung Seni Daya Sundas ability to thrive in society, particularly in the Bandung Zoo area. The theory used in this book is Alan P. Merriams functional theory. In contrast, the method used is a qualitative method with data collection techniques that focus on observation, interpretation, and documentation. The findings of this study show that Ketuk Tilu Lingkung Seni Daya Sunda in Bandung Zoo can sustain its existence by providing the following services to the community: 1) The Function of Emotional; 2) The Function of Entertainment; 3) The Function of Communication; dan 4) The Function of The Integration of Society. Keyword: Ketuk Tilu, Existence, Bandung Zoo